2020
DOI: 10.1002/msc.1478
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences and satisfaction at one year following primary total knee arthroplasty: A focus‐group discussion

Abstract: Objective: To date, no study has explored patients' experiences, outcome expectations and satisfaction 1-year post-total knee arthroplasty (TKA) using focus-group discussion (FGD). The exploration of patients' expectations, functional recovery and limitations may support future modifications and thus improve outcomes post-TKA. Methods: An FGD was conducted with patients at 1-year post-TKA. Moderators led the discussion using a semistructured discussion guide. The discussion was digitally recorded, transcribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…and the views study. The only finding of note was that one outcomes study did not identify any significant benefits of an acupuncture plus exercise intervention [61], contrasting with the perceived value of acupuncture reported by Bin Sheeha et al [75].…”
Section: Views Studiesmentioning
confidence: 81%
See 3 more Smart Citations
“…and the views study. The only finding of note was that one outcomes study did not identify any significant benefits of an acupuncture plus exercise intervention [61], contrasting with the perceived value of acupuncture reported by Bin Sheeha et al [75].…”
Section: Views Studiesmentioning
confidence: 81%
“…In a consensus development study by Westby et al [30], a proposed quality indicator (QI) states that patients undergoing TKR should commence an individually tailored, progressive exercise program at least 8 weeks pre-operatively and lists specific exercise components that should be included. Bin Sheeha et al [75] conducted a qualitative study in which two participants reported that they valued receiving pre-operative exercise guidance from a physiotherapist. Conversely, three participants did not recommend pre-operative physiotherapy because they did not find it helpful or felt that the same exercises could be obtained online [75].…”
Section: Views Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be used to explore the outcomes that cannot be explained statistically. Responses in FGD are spoken open-ended, relatively broad, and qualitative (13). They have more depth and variety.…”
Section: Introductionmentioning
confidence: 99%